Influence of oral health related behavior on oral health of adolescents in Belgrade - Lalić Maja; Krivokapić Marina; Janković-Bukva Biljana; Aleksić Ema; Gajić Mihajlo; Banković Dušica (Serbian Medical Society - Dental Section, Belgrade, 2013)
Introduction. Adolescence is a period of intensive physical, psychological and emotional changes that might affect existing oral health related habits and result in developing risky behaviors. The aim of the present study was to investigate oral health attitudes and behavior and their relation to dental caries experience in the group of adolescents from Belgrade. Material and Methods. This cross-sectional study included 404 high-school students grade one from Belgrade. Two trained and calibrated dentists conducted clinical examination in classrooms to determine oral health status of adolescents (DMFT index and visual signs of gingivitis). Modified Serbian version of Hiroshima University Dental Behavior Inventory (HU-DBI) questionnaire with three additional questions was used to collect data on oral health behavior and attitudes. Results. Mean HU-DBI score was 6.22±1.45 for males and 6.28±1.45 for females (p<0.05). Dental visits at least once in a year reported 67.3% adolescents, more often girls (p<0.05). Only emergency dental visits reported 47.1% of adolescents. Majority of respondents reported brushing teeth twice a day or more (86.2%), girls more often than boys (p<0.001). Only 13.4% reported regular flossing and 30.3% daily use of mouth rinses. Mean DMFT score was 5.84±0.20 with 45% of untreated decayed tooth. Unfavorable oral health related attitudes and behavior were related to poorer oral health status of adolescents. Conclusion. Poor oral health of adolescents is influenced by their inadequate attitudes and habits. Program of oral health promotion for adolescents that would target knowledge, attitudes and skills development should be implemented to enhance adolescents' oral self-care regime and oral health outcome.